Cardiac Dysfunction Following Brain Death in Children. Issue 4 (May 2015) - Krishnamoorthy, Vijay; Borbely, Xenia; Rowhani-Rahbar, Ali; Souter, Michael J.; Gibbons, Edward; Vavilala, Monica S.
<x xml:space="preserve">Abstract</x> Objectives: Cardiac dysfunction has been reported to occur in as much as 42% of adults with brain death, and may limit cardiac donation after brain death. Knowledge of the prevalence and natural course of cardiac dysfunction after brain death may help to improve screening and transplant practices but adequately sized studies in pediatric brain death are lacking. The aims of our study are to describe the prevalence and course of cardiac dysfunction after pediatric brain death. Design: Cross-sectional study. Setting/Subjects: We examined an organ procurement organization database (Life Center Northwest) of potential pediatric cardiac donors diagnosed with brain death between January 2011 and November 2013. Intervention: Transthoracic echocardiograms were reviewed for cardiac dysfunction (defined as ejection fraction <50% or the presence of regional wall motion abnormalities). Descriptive statistics were used to analyze clinical characteristics and describe longitudinal echocardiogram findings in a subgroup of patients. We examined for heterogeneity between cardiac dysfunction with respect to cause of brain death. Measurement and Main Results: We identified 60 potential pediatric cardiac donors (age ⩽ 18 yr) with at least one transthoracic echocardiogram following brain death. Cardiac dysfunction was present in 23 patients (38%) with brain death. Mean ejection fraction (37.6% vs 62.2%) and proportion of procured hearts (56.5% vs 83.8%) differed significantly between the groups with and without cardiac dysfunction, respectively. Of the 11 subjects with serial transthoracic echocardiogram data, the majority of patients with cardiac dysfunction (73%) improved over time, leading to organ procurement. No heterogeneity between cardiac dysfunction and particular causes of brain death was observed. Conclusion: The frequency of cardiac dysfunction in children with brain death is high. Serial transthoracic echocardiograms in patients with cardiac dysfunction showed improvement of cardiac function in most patients, suggesting that initial decisions to procure should not solely depend on the initial transthoracic echocardiogram examination results.